Association of atrial fibrillation and various cancer subtypes. Issue 5 (17th July 2021) - Zubair Khan, Muhammad; Gupta, Ashwani; Patel, Kirtenkumar; Abraham, Aida; Franklin, Sona; Kim, Do young; Patel, Krunalkumar; Hussian, Ishtiaq; Zarak, Muhammad Samsoor; Figueredo, Vincent; Kutalek, Steven
Abstract: Background: Studies have shown that the incidence of atrial fibrillation (AF) in cancer is most likely due to the presence of inflammatory markers. The purpose of our study is to determine the association of AF with different cancer subtypes and its impact on in‐hospital outcomes. Methods: Data were obtained from the National Inpatient Sample database between 2005 and 2015. Patients with various cancers and AF were studied. ICD‐9‐CM codes were utilized to verify variables. Patients were divided into three age groups: Group 1 (age < 65 years), Group 2 (age 65‐80 years), and Group 3 (age > 80 years). Statistical analysis was performed using Pearson chi‐square and binary logistic regression analysis to determine the association of individual cancers with AF. Results: The prevalence of AF was 14.6% among total study patients (n = 46 030 380). After adjusting for confounding variables through multivariate regression analysis, AF showed significant association in Group 1 with lung cancer (odds ratio, OR = 1.92), multiple myeloma (OR = 1.59), non‐Hodgkin lymphoma (OR = 1.55), respiratory cancer (OR = 1.55), prostate cancer (OR = 1.20), leukemia (OR = 1.12), and Hodgkin's lymphoma (OR = 1.03). In Group 2, the association of AF with multiple myeloma (1.21), lung cancer (OR = 1.15), Hodgkin lymphoma (OR = 1.15), non‐Hodgkin lymphoma (OR = 1.12), respiratory cancer (OR = 1.08), prostate cancer (OR = 1.06), leukemia (OR = 1.14), and colon cancer (OR = 1.01) were significant. In Group 3, AF showed significant association with non‐Hodgkin lymphoma (OR = 1.06), prostate (OR = 1.03), leukemia (OR = 1.03), Hodgkin's lymphoma (OR = 1.02), multiple myeloma (OR = 1.01), colon cancer (OR = 1.01), and breast cancer (OR = 1.01). The highest mortality was found in lung cancer in age <80 and prostate cancer in age >80. Conclusion: In patients age <80 years, AF has significant association with lung cancer and multiple myeloma, whereas in patients age >80 years, it has significant association with non‐Hodgkin lymphoma and prostate cancer. In patients age <80 years, increased mortality was seen in AF with lung cancer and in patients age >80 years, increased mortality was seen in those with AF and prostate cancer. Twitter Abstract: In age <80, lung cancer and multiple myeloma have a strong association with AF while thyroid and pancreatic cancers have no association with AF at any age. In age greater than 80, NHL and prostate cancer have a significant association with AF. Abstract : Our study found that in age <80, lung cancer and multiple myeloma have a strong association with AF while thyroid and pancreatic cancers have no association with AF at any age. In age greater than 80, NHL and prostate cancer have a significant association with AF. The highest mortality incidence in age <80 was found in lung cancer and in age >80 was seen in prostate cancer